Application of 3D modeling in managing planning control and improving public participation - Hj. Mohd. Noor, Norzailawati
The increasingly complex system that integrated into the modern city have always being the headache for the planner to understand and plan for their territory. With the development of advanced technology, the three-dimensional visualization technology has been developed and being improved day-to-day to help the urban planning fields especially in the decision making. Therefore, this research is an attempt to identify the application of 3D modelling in managing the planning control as well as improving the efficiency of public participation. This 3D modelling has been developed using CityEngine, The objectives have been formulated identifying the application of 3D modeling in planning control in term of development density and plot ratio and To analyze the criteria can be used in modeling the development scenarios. The method for this application is using the CGA rules which were applied to the GIS data that imported for ArcGIS software. The finding illustrates how the GIS layer generated into three-dimensional buildings, which have some features that can be used to control the urban planning. In addition, the 3D model has been exported to be visualizing using Web Scene interface that enable the user to view the scenarios in side-by-side viewport. Thus, it is recommended that this system would be implemented in the local authorities to improve the urban planning system.